Joseph Roberts Smallwood : masthead Newfoundlander, 1900-1949 - Baker, Melvin; Neary, Peter, 1938- (McGill-Queen's University Press, 2021)
"No other figure, historical or political, features more prominently in recent Newfoundland history than Joey Smallwood. During his long career in Newfoundland politics, Smallwood used the literary, rhetorical, and theatrical skills honed in the first five decades of his life to create a distinct and celebrated persona. He authored the narrative of his own life and told his story in his lively autobiography, I Chose Canada, published in 1973 only a year after he left office. Talented, venturesome, and above all resilient, he was no ordinary Joe. Smallwood was born in Gambo, Bonavista Bay, but grew up in St John's. Leaving school at fifteen, he quickly established himself as a journalist and as a publicist for Sir William Coaker's Fishermen's Protective Union. In the early 1920s Smallwood sojourned twice in New York, where he planned a Newfoundland labour party. Ambition, however, led him to support the Liberal Party of Sir Richard Squires. Defeated as a candidate in the general election of June 1932, he next promoted producer and consumer cooperatives, but with mixed results. In 1937 he edited The Book of Newfoundland and thereafter enjoyed great success on the radio as 'The Barrelman.' The book culminates with Smallwood's adoption of the cause of Confederation and his swearing in on 1 April 1949 as premier of the new Province of Newfoundland. There are multiple J.R. Smallwoods, but the aspiring and ambitious figure presented in this biography stands apart. Melvin Baker and Peter Neary use the largely untapped sources of Smallwood's own papers and his extensive journalistic writing to add a documentary basis to what is known or conjectured about the first five decades of Smallwood's remarkable life, both public and private."--